Asian Pacific Organization for Cancer Prevention (APOCP) - Moore, Malcolm (Indonesian Journal of Cancer, 2009)
https://www.scribd.com/doc/45478099/Asian-Pacific-Organization-for-Cancer-Prevention-APOCP